HEAD TEACHERS’ MANAGEMENT STRATEGIES AND PARENTAL SUPPORT IN SPECIAL PRIMARY SCHOOLS IN LAGOS STATE, NIGERIA - Christopher Oluwatoyin Fashiku; Ezegwu Chidimma Gloria; Yusuf Abubakar Abiola; Fashiku Bunmi Comfort (The University of Kuningan, 2021)
The study investigated management strategies of Head teachers and parental support in special primary schools in Lagos state, Nigeria.The study adopted the descriptive survey research design. The population for the study comprised all the The study investigated management strategies of Head teachers and parental support in special primary schools in Lagos state, Nigeria.The study adopted the descriptive survey research design. The population for the study comprised all the seven School Heads and teachers in the special schools as well as all Parent Teacher Association (PTA) members in the schools. A sample of 31 respondents was used, 21 respondents were selected using the cluster sampling technique while 10 PTA members were sampled using the convenient sampling technique. The instruments used in the study for collecting data were a self-designed questionnaire titled “Influence of Management Strategies on Parental Support Questionnaire” (IMSPSQ) and an interview guide titled ‘Influence of Management Strategies on Parental Support Interview Guide’ (IMSPSIG).The validity and reliability of the instruments were ensured before use. Percentage and frequency counts were used to analyse the data collected. The result showed among others that providing parental support skill acquisition programmes, effective communication with parents, providing opportunities for parents to suggest ideas, involving different stakeholders and adoption of decentralized decision making approach were the various management strategies adopted in special primary schools in Lagos state. The result also showed that the level of influence of management strategies on parental support in special primary schools in Lagos State was moderate. The study recommended that government and other concerned organizations and bodies should sensitize schools and organize training programmes, seminars or conferences for Head Teachers and classroom teachers in primary schools on the importance of involving parents in school management.Key words: Management, Strategies, Parental Support, Special, Primary-Schools